KOLABORASI ETNOMATEMATIKA JAWA DAN MADURA DALAM PEMBELAJARAN BERBASIS LESSON STUDY TERHADAP PENALARAN ALJABAR SISWA - Nur Fitriyah Indraswari; Kurratul Aini; Abd. Azis; Widadatus Sa'baniyah; Siti Qamariyah; Jihat Nurrahman (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The low level of students’ algebraic reasoning in solving problems on solid geometry material and the limited integration of cultural values in mathematics learning became the background of this study. This research aims to describe the implementation of the collaboration of Javanese–Madura ethnomathematics in lesson study–based mathematics learning and to examine its effect on the algebraic reasoning of students at MIS Al-Maarif Bungah Gresik. The study employed a mixed-method approach with a sequential mixed methods strategy, in which quantitative data were analyzed in the first phase and qualitative data in the second phase. The research instruments consisted of lesson study observation sheets, interviews, and an algebraic reasoning test based on the indicators of understanding problems, making generalizations, forming general algebraic expressions, and solving problems. The sample consisted of 30 fifth-grade students at MIS Al-Maarif Bungah Gresik selected through purposive sampling. Quantitative data were analyzed using n-gain and paired sample t-test, while qualitative data were analyzed using thematic descriptive techniques from observations and interviews. The quantitative findings showed an average pretest score of 50.37 and a posttest score of 78.80, with an n-gain value of 0.646 (moderate category). The paired sample t-test resulted in tcount = 38.961 > ttable= 1.690, indicating a significant difference between the pretest and posttest results. The qualitative findings revealed an increase in students’ enthusiasm and conceptual understanding, along with a need for continuous practice in the generalization indicator. In conclusion, the collaboration of Javanese–Madura ethnomathematics in lesson study–based learning has a positive effect on students’ algebraic reasoning. These findings imply that the lesson study–based Javanese–Madura ethnomathematics collaboration can be applied practically to improve elementary school students’ algebraic reasoning.